2019
DOI: 10.3390/ijerph16050737
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Sensitization and Asthma Outcomes among World Trade Center Rescue and Recovery Workers

Abstract: A large number of World Trade Center (WTC) rescue and recovery workers are affected by asthma. While physical and mental health comorbidities have been associated with poor asthma control in this population, the potential role of allergen sensitization is unknown. This study examined the association of indoor sensitization and exposure as a risk factor for increased asthma morbidity in WTC workers. We used data from a prospective cohort of 331 WTC workers with asthma. Sensitization to indoor allergens was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The absence of peripheral blood Type 2 (T2) inflammatory signals in most of our patients is similar to the findings of Malo et al, who reported on long-term findings in a small group of subjects with irritant-induced asthma [69]. Our findings are also consistent with studies of WTC community members in which low FeNO values or IgE were identified, or in which elevated levels were identified in only a subset of patients with persistent respiratory symptoms [14,16,48,54,55]. The findings are also consistent with studies in firefighters, in which only a subset displayed persistently elevated eosinophil levels associated with decline in lung function [49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The absence of peripheral blood Type 2 (T2) inflammatory signals in most of our patients is similar to the findings of Malo et al, who reported on long-term findings in a small group of subjects with irritant-induced asthma [69]. Our findings are also consistent with studies of WTC community members in which low FeNO values or IgE were identified, or in which elevated levels were identified in only a subset of patients with persistent respiratory symptoms [14,16,48,54,55]. The findings are also consistent with studies in firefighters, in which only a subset displayed persistently elevated eosinophil levels associated with decline in lung function [49].…”
Section: Discussionsupporting
confidence: 92%
“…Poor asthma control is usually ascribed to poor adherence with prescribed medications [ 14 , 54 , 55 , 56 , 57 ] and we assumed that many of the persistent symptoms in the WTC EHC patients would be due to failure to use appropriate medications. We therefore presumed that LRS would improve with adherence to a treatment of ICS/LABA and designed a run-in period to confirm adherence before defining study status as Uncontrolled or Controlled.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that self-management behaviors beyond medication adherence, such as lack of trigger avoidance behaviors or patients' illness and medication beliefs (24), may have affected control in this population. An alternative explanation may be that mental health disorder such as PTSD, anxiety, and depression may increase the risk of factors such as obesity and smoking behaviors, poor sleep, low physical activity, or daily stressors that may in turn lead to poor control (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of allergen sensitization based only on skin test results in a multiethnic Asian cohort with severe asthma was as high as 78.2%, with sensitization to more than a single allergen in most cases [ 15 ]. Rojano et al showed that patients with asthma are sensitized mostly to house dust mites (34%); however, pet sensitizations were also common (cat—33% and dog 21%) [ 16 ]. Kleine-Tebbe et al also investigated patients with severe asthma and, in this group, similar allergens were found with more sensitizations in general (HDM—39%, cat—34%, dog—31%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%